Revision notes for MCEM Part A - Harrison, Mark, Dr. (Oxford : Oxford University Press, 2011)
A concise revision guide for one of the most difficult parts of the MCEM examination, covering the anatomy and basic sciences that will be tested in the Part A paper. Presented in note form and with high quality explanatory diagrams, this book will equip candidates with the knowledge needed to pass the examination.
Includes index.
Description based on print version record.
Keywords: Emergency medicine -- Examinations -- Study guides